Factors Affecting the Utilization of Posyandu for the Elderly in the Working Area of the Glugur Darat Health Center, East Medan District, Medan City - Pandiangan, Marintan; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
Posyandu (Integrated Service Post) for the Elderly is a community resource health service (UKBM) forum to serve the elderly population, whose formation and implementation process is carried out by the community together with non-governmental organizations (NGOs), across government and non-government sectors, the private sector, social organizations and others, with an emphasis on health services on promotive and preventive efforts. The purpose of the study is to find out the factors that affect the utilization of elderly posyandu in the Working Area of the Glugur Darat Health Center, East Medan District, Medan City. The research design uses the Analytical Survey method with a Cross Sectional approach. The population in this study is all elderly as many as 11,050 people. The sample was 99 with stratified random sampling. Data analysis uses univariate, bivariate and multivariate analysis. The results of logistic regression showed that there was an influence of knowledge p = 0.008, perception p = 0.006, distance p = 0.003 and family support p = 0.002, while what did not have an influence was the attitude and support of health workers towards the utilization of posyandu for the elderly in the Working Area of Glugur Darat Health Center, East Medan District, Medan City, the dominant factor was family support p = 0.000 Exp (B) 41,303 with 95% CI = 5,389-316,539. The conclusion of this study is that there is an influence of knowledge, perception, distance and family support on the utilization of elderly posyandu in the Working Area of the Glugur Darat Health Center, East Medan District, Medan City. It is recommended to the Glugur Darat Health Center to further increase its participation in providing training to health workers and be able to promote the use of elderly posbindu and it is better for Door To Door health workers to provide counseling on the use of elderly posbindu.